Abnormal Pap smear among pregnant women – Feasibility of opportunistic cervical screening - Nur Farihan Mukhtar; Beng Kwang Ng; Suria Hayati Md Pauzi; Yin Ping Wong; Mohammad Rafi’uddin Hamizan; Pei Shan Lim; Nurismah Md Isa (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2023)
Objective: The uptake of cervical cancer screening is poor, especially in developing countries. Thus, pregnancy represents a good opportunity to have the test done. The aim of this study is to determine the prevalence of abnormal Pap smear among pregnant women during their antenatal check-ups. Study design: A prospective study involving five hundred and ninety-six women was recruited over a 1-year duration from 15th January 2018 until 14th January 2019 in a tertiary referral center, in Malaysia. Pap smears were performed on all consented pregnant women using liquid-based cytology and the results were obtained to evaluate the prevalence of abnormal Pap smear during pregnancy. Maternal risk factors associated with abnormal Pap smear were identified and the outcomes of abnormal Pap smear were followed up. Results: A total of 670 participants were approached and 596 participants agreed to participate, giving a response rate of 89.0 %. Therefore, 587 participants were available for analysis. There were nine unsatisfactory smears (1.5 %). The prevalence of premalignant lesions reported on p % ap smear was 0.8 %. Three respondents had atypical squamous cells of undetermined significance (ASCUS) (0.5 %) and two respondents had low-grade squamous intraepithelial lesions (LSIL) (0.3 %). Almost one-third (30.3 %) of respondents had an infection and 24 (4.1 %) smears were reported as reactive changes associated with inflammation. Respondents between the age of 20–30 years old had a significant association with an abnormal pre-cancerous smear (p = 0.000) as well as nulliparity (p = 0.0.40). There was no significant association between height, weight, BMI, sexual partner, age of first intercourse, smoking habit, history of sexually transmitted disease and history of abnormal Pap smear. Conclusion: The prevalence of abnormal pre-cancerous smears during pregnancy is low. However, it is desirable to perform cervical screening as it provides an opportunity to no screening at all.